Effectiveness of ambon banana stem juice as immunostimulatory against Aeromonas hydrophila infections in catfish Clarias gariepinus - Qorie Astria; Sri Nuryati; Kukuh Nirmala; Alimuddin Alimuddin (Jurnal Akuakultur Indonesia)
ABSTRACT